Biochemical and enzymatic alterations of watermelon associated with irrigation management and inoculation with Rhizobacteria - de Araújo, Mycaella Gonçalves (2025)
Water stress has caused major losses in the agricultural productivity of crops, inducing the search for alternatives for sustainable cultivation. In this context, the objective of this study was to evaluate the tolerance of watermelon under water stress, inoculated with bacterial strains of the genus Bacillus spp., regarding the biochemical and enzymatic variables in the flowering stage. A randomized block design was adopted in a split-plot 4x4 factorial scheme, with plots consisting of four levels of soil water availability (40%, 60%, 80% and 100% of field capacity - FC) and subplots consisting of four inoculations (Negative Control (NC); XX6.9 bacteria; P6.2 bacteria; MIX – co-inoculation of XX6.9 and P6.2 bacteria), with five replicates. XX6.9 bacteria and NC were the treatments most affected by severe water stress, since at the soil water availability (SWA) level of 40% FC they showed high contents of the oxidative marker (MDA) and proline. Although the inoculation with XX6.9 bacteria promoted a higher content of osmoregulators such as proteins, total soluble sugars and reducing sugars, it was not enough to attenuate the effects of water deficit. On the other hand, treatments with P6.2 bacteria and MIX of bacteria showed reduced levels of MDA at the SWA level of 40% FC, accompanied by high enzymatic activity of POD and CAT, which may contribute to the tolerance of the watermelon crop to water stress.